2014
DOI: 10.4209/aaqr.2012.11.0323
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study of Surface O3, NOx, CH4 and Total NMHCs at Kannur, India

Abstract: This paper presents the results of measurements of the surface ozone (O 3 ), oxides of nitrogen (NO x ), methane (CH 4 ) and total non-methane hydrocarbons (TNMHCs) in a rural coastal location at Kannur (11.9°N, 75.4°E, 5 m asl), India from November 2009 to December 2011. The diurnal cycle for surface O 3 had a peak in the afternoon and declined during nighttime. The maximum and minimum mixing ratio of surface O 3 was observed in winter and monsoon seasons respectively. NO x concentration was high during mid-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…After sunrise, the air becomes unstable and then turbulence develops along with the atmospheric boundary layer (Wang and Wang, 2014;Stull, 1988). Prior studies (Gaur et al, 2014;Nishanth et al, 2014) reported different behavior in the diurnal patterns of NO and NO 2 concentrations where they were found higher concentrations in between 08:00 to 10:00 h LST and 19:00 to 23:00 h LST. Seasonally, less variability was observed with similar trend during midnight to until 08:00 h LST in every season except for the evening peaks (17:00-21:00 h LST) in the post-monsoon and winter seasons.…”
Section: Diurnal Variability Of Gaseous Pollutants and Pmmentioning
confidence: 92%
See 1 more Smart Citation
“…After sunrise, the air becomes unstable and then turbulence develops along with the atmospheric boundary layer (Wang and Wang, 2014;Stull, 1988). Prior studies (Gaur et al, 2014;Nishanth et al, 2014) reported different behavior in the diurnal patterns of NO and NO 2 concentrations where they were found higher concentrations in between 08:00 to 10:00 h LST and 19:00 to 23:00 h LST. Seasonally, less variability was observed with similar trend during midnight to until 08:00 h LST in every season except for the evening peaks (17:00-21:00 h LST) in the post-monsoon and winter seasons.…”
Section: Diurnal Variability Of Gaseous Pollutants and Pmmentioning
confidence: 92%
“…The precursors of O 3 can be transported over long distances from source regions, strongly influenced by meteorological processes (Brankov et al, 2003). Formation rates of O 3 are proportional to temperature and solar intensity (Nishanth et al, 2012(Nishanth et al, , 2014. Furthermore, O 3 contributes to global warming (IPCC, 2013), being one of the most important greenhouse gases.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous observations and studies of surface O 3 in India began about 30 years ago and are currently underway in more than 20 various locations [14,24,60,62,76,[101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118]. The diurnal and seasonal variation of surface O 3 over Kannur shows a classic profile of a rural area, which is strongly prejudiced by seasonal changes, similar to other places in India.…”
Section: Comparison Of O 3 With Other Observational Sitesmentioning
confidence: 99%
“…Ozone at ground level acts as a strong oxidant and thus is detrimental to human health and vegetation [3]. The trace gases not only have an impact on the air quality of a particular environment but also play a role in modulating the earth's climate by modifying the radiation and energy balance of the earth's atmosphere [4][5][6]. Due to industrialization, urban developments and transport, gases such as Carbon Monoxide, Nitrous Oxides, Methane, VOCs are emitted which are chemically involved in producing tropospheric ozone.…”
Section: Introductionmentioning
confidence: 99%
“…Due to industrialization, urban developments and transport, gases such as Carbon Monoxide, Nitrous Oxides, Methane, VOCs are emitted which are chemically involved in producing tropospheric ozone. Ozone in troposphere also occurs by transport of air from the stratosphere [4,5,7]. The ozone concentration in tropical countries is also contributed from biomass burning especially forest fires [8][9][10].…”
Section: Introductionmentioning
confidence: 99%